2011
DOI: 10.5951/mtms.16.6.0346
|View full text |Cite
|
Sign up to set email alerts
|

Tell a Piecewise Story

Abstract: By focusing on slope and using dynamic software, students develop the ability to describe functions in a geometry context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The walk-a-graph activity provided real-life data, not only quasi real-life data as is most common in school mathematics. In addition, using their own body as moving object may have made the experience even more realistic to the students than moving a fictional character on screen as in the SimCalc project (Roschelle et al, 2010) or the approach described by Sinclair and Armstrong (2011). Data from the Q-sorting activity showed that the lessons reported on here may have had positive impact on the epistemological obstacles as highlighted by Sierpinska (1992), like attitudes and beliefs.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The walk-a-graph activity provided real-life data, not only quasi real-life data as is most common in school mathematics. In addition, using their own body as moving object may have made the experience even more realistic to the students than moving a fictional character on screen as in the SimCalc project (Roschelle et al, 2010) or the approach described by Sinclair and Armstrong (2011). Data from the Q-sorting activity showed that the lessons reported on here may have had positive impact on the epistemological obstacles as highlighted by Sierpinska (1992), like attitudes and beliefs.…”
Section: Discussionmentioning
confidence: 84%
“…To support the learning of functions, many different kinds of digital tools have been used (e.g., Roschelle et al, 2010;Sinclair & Armstrong, 2011;Tan, Hedberg, Koh, & Seah, 2006). Regardless of point of view on learning outcomes from using technological tools, it is important to realize that use of technology is more than the introduction of new tools.…”
Section: Discussionmentioning
confidence: 99%